PROSPECTS OF USING CREATIVITY IN THE PRESCHOOL EDUCATION SYSTEM - Saydullaeva Nargis Ilhomovna (International Scientific and Current Research Conferences, 2023)
Preschool education plays a crucial role in shaping a child's cognitive, social, and emotional development. Traditionally, early childhood education has focused on imparting basic academic skills and knowledge. However, there is a growing recognition of the importance of integrating creativity into the preschool education system. This article explores the prospects of using creativity as a central component of early childhood education, discussing its benefits, challenges, and potential implications for the future.